2022
DOI: 10.1111/1756-185x.14407
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine resistance: Associated factors and its effect on health‐related quality of life in patients with familial Mediterranean fever

Abstract: Aim To determine the factors associated with colchicine resistance and the effect of colchicine resistance on health‐related quality of life (QoL) in patients with familial Mediterranean fever (FMF). Methods Demographic and clinical features, MEFV gene mutations, and Pras disease severity scores were recorded. QoL was assessed using the Short Form‐36 (SF‐36) and FMF‐QoL scales. Colchicine resistance was defined as at least 1 attack per month for 6 months at the maximum tolerated dose of colchicine in fully com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The reason is probably the more profound serosal inflammation in severe FMF. The frequency of chest pain is 35–60% in colchicine-resistant FMF patients in the literature, which may differ according to the ethnic group [ 7 , 8 , 15 , 17 , 24 ]; this frequency was 30% in our study. Another factor could be that chest pain is more frequent among patients with exon 10 mutations [ 25 , 26 ], and the majority of colchicine-resistant patients have exon 10 MEFV mutations.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…The reason is probably the more profound serosal inflammation in severe FMF. The frequency of chest pain is 35–60% in colchicine-resistant FMF patients in the literature, which may differ according to the ethnic group [ 7 , 8 , 15 , 17 , 24 ]; this frequency was 30% in our study. Another factor could be that chest pain is more frequent among patients with exon 10 mutations [ 25 , 26 ], and the majority of colchicine-resistant patients have exon 10 MEFV mutations.…”
Section: Discussionmentioning
confidence: 41%
“…Acute arthritis could occur during attacks, but also FMF patients more frequently have chronic arthritis [ 1 ]. Arthritis was observed in ≈30–50% of FMF patients who were colchicine resistant [ 7 , 17 , 24 ] and was present in 35% of colchicine-resistant patients in our cohort. In a recent study by Omma et al [ 24 ], the only significant difference between colchicine-resistant and colchicine-responsive FMF patients was the higher frequency of arthritis among colchicine-resistant patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In recent studies, colchicine has been found to have a substantial influence on morphological, biochemical and anatomical traits of different plants species which ultimately determine the effectiveness of their fluorescence and physiological activities [ 9 ]. However, it is highly toxic to human health and unsafe to the environment at elevated levels [ 10 ]. In plants, the elevated levels of colchicine also lead to deformities and diminish their growth and productivity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much research is available on creating, assessing, and applying health-related quality of life (HRQoL) metrics in public health. [1][2][3] Thus, the significance of life expectancy and HRQoL in the years before death has come to the attention of researchers and doctors worldwide. [1,4] For instance, there were significantly more publications in PubMed using the search term "HRQoL" from the medical subject headings between 1986 and 2021 (Fig.…”
Section: Introductionmentioning
confidence: 99%